Non-Ossifying Fibroma Mimicking Extra-Neural Metastasis in Pediatric Cerebral Anaplastic Ependymoma: A Case Report - Davaa, Munkhgerel; Enkhjargal, Manduul; Bat-Arildii, Ariuntungalag; Ganbold, Mungunbagana; Dashjamts , Tuvshinjargal; Khashbat, Delgerdalai (Central Asian Journal of Medical Sciences, 2024)
Objective: This case report focuses on the differential diagnosis of non-ossifying fibroma and extra-neural metastasis in pediatric cerebral anaplastic ependymoma. Methods: Magnetic resonance imaging, computed tomography, positron emission tomography, and biopsy were performed. Results: An 11-year-old patient who had undergone surgical removal of an anaplastic ependymoma was referred for a positron emission tomography examination for follow-up. The positron emission tomography revealed a fluorodeoxyglucose-avid lesion in the left proximal tibia, raising suspicion of bone metastasis. Subsequently, a biopsy was performed, and the lesion was confirmed to be a non-ossifying fibroma. Conclusion: This case highlights that imaging features of bone lesions on positron emission tomography scans should be correlated with findings of conventional imaging modalities to improve diagnostic accuracy and prevent unnecessary invasive procedures in oncology patients.